Personal Correspondence - Abrahams, Peter (My University, 1964)
Correspondence from The Dramatists Guild to Peter Abrahams, prompting him to make his membership payments. Includes invoice of arrears.
3 pgs. Typed scripted, Sepia-Toned, good condition.
Keywords: Records and correspondence; Dramatists. American